2021
DOI: 10.1186/s13018-021-02210-1
|View full text |Cite
|
Sign up to set email alerts
|

Genipin and insulin combined treatment improves implant osseointegration in type 2 diabetic rats

Abstract: Background Type 2 diabetes mellitus (T2DM) has a harmful effect on the stability and osseointegration of dental implants. T2DM induces mitochondrial damage by inhibiting AMPK signaling, resulting in oxidative stress and poor osteogenesis in the peri-implant bone area. Genipin is a major component of gardenia fruits with strong antioxidant, anti-inflammation, and antidiabetic actions, and it also can activate mitochondrial quality control via the AMPK pathway. The purpose of this study was to in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Adiponectin, a cytokine, could also improve the osteointegration of implants by rescuing mitochondrial impaired through the AMPK pathway under diabetic conditions, both in vivo and in vitro. 5 , 66 Selenomethionine, a naturally occurring amino acid-containing selenium, could attenuate H 2 O 2 -induced suppression of the osteogenic differentiation of BMSCs through an antioxidant effect that was modulated by PTEN/PI3K/AKT pathway, which could be a promising antioxidant candidate by which to reduce oxidative stress during dental implant osteointegration process. 67 Our study, in combination with previous studies, showed that ADNP and GDF11 may affect the metabolic process and antioxidant functions of DM-BMSCs, which could thus be a crucial target by which to address implant stability and bone integration in patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adiponectin, a cytokine, could also improve the osteointegration of implants by rescuing mitochondrial impaired through the AMPK pathway under diabetic conditions, both in vivo and in vitro. 5 , 66 Selenomethionine, a naturally occurring amino acid-containing selenium, could attenuate H 2 O 2 -induced suppression of the osteogenic differentiation of BMSCs through an antioxidant effect that was modulated by PTEN/PI3K/AKT pathway, which could be a promising antioxidant candidate by which to reduce oxidative stress during dental implant osteointegration process. 67 Our study, in combination with previous studies, showed that ADNP and GDF11 may affect the metabolic process and antioxidant functions of DM-BMSCs, which could thus be a crucial target by which to address implant stability and bone integration in patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“… 4 A previous study also reported that insulin-treated T2DM rats had improved bone regeneration and trabecular microstructure to some extent, but not comparable to the control group. 5 Furthermore, a recent clinical study discovered that T2DM patients with good glycaemic control had lower implant stability during the healing stage than patients without diabetes. 6 It is thus clear that we need to improve our knowledge regarding the key factors that affect implant failure in patients with diabetes in order to improve the success rate of implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, multiple pharmacological activities of geniposide and its aglycone genipin have been reported, including its hepatoprotective effect [ 3 ], hypoglycemic [ 4 ] and anti-inflammatory activity [ 5 ], protection of cerebral ischemic injury [ 6 ], neuroprotection [ 7 ], and anti-depressant effects [ 8 ]. Although geniposide has been widely considered as the main active component, some studies suggested that genipin was a more active ingredient [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genipin (GE) has been shown to be an effective treatment for retinal pigment epithelium injury through the development of diabetes drugs (9). Derived from the extraction and purification of gardenia jasminoides, GE has effective anti-inflammatory, antioxidant, and anti-diabetes properties (10).…”
Section: Introductionmentioning
confidence: 99%